INTERPRETATION OF HIGH-RESOLUTION IMAGES FOR IDENTIFICATION OF DAMAGE TO RASANG AND LOST SHIP IRRIGATION CHANNEL KOTO TANGAH SUB-DISTRICT, PADANG CITY - Liza Septi Dhamara Asri; Triyatno Triyatno (International Remote Sensing Applied Journal, 2022)
This type of research is quantitative descriptive, with image interpretation through high-resolution images, and primary data as a source of data obtained through field surveys. The technique for determining informants is Total Sampling. The population in this study are villages in the Koto Tangah District, Padang City. This analysis uses quantitative analysis, namely on-screen digitization using the Arcgis application. Based on the results of research and discussion on High-Resolution Image Interpretation for Identification of Irrigation Channel Damage in Kasang and Kapalo Hilalang, Koto Tangah District, Padang City, the results obtained, namely the identification of irrigation canals using high-resolution imagery produces sufficient data in accordance with the conditions field. Based on the field survey, the condition of the network damage for the Hilalang Headquarters, starting from the weir building to BKH 1 was heavily damaged, BKH 2 to BKH 6 was moderately damaged. Starting from BKH 7 to BKH 8 still has good conditions. While the condition of the Kasang II irrigation canal from the weir to BKD 5 is still in good condition. BKD 6 to BKD 7 is moderately damaged. In contrast to BKD 4, it is in good condition, while parts of BAA 1 to 3 are in moderately damaged condition. The shape of the irrigation image in the city of Padang is tortuous, this is influenced by the topography of the area around the river which consists of community rice fields. The pattern shown in the image of the irrigation canal in the city of Padang is elongated, this shows the flow of the river from the upstream area to the downstream area of ​​the river. The texture that is displayed in the image of the irrigation canal in the city of Padang has a smooth texture. The site shown in the image of the irrigation canal in the city of Padang is side by side with the rice fields belonging to the community in the Koto Tangah District.